Foot strike posture and lower-limb dynamics during sidestepping among elite female athletes: Implications for ACL injury risk - Chinnasee, C.; Weir, G.; Alderson, J.; Sasimontonkul, S.; Donnelly, C. J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to compare the lower-limb dynamics between fore-foot (FF) and rear-foot (RF) strike patterns during unplanned sidestepping. Three-dimensional (3D) motion capture data were collected from 16 elite female hockey players. Ankle, knee, and hip: angle at initial foot contact (IC), range of motion (ROM), peak moment, and negative peak net joint power during weight acceptance phase were compared between athletes using natural RF and FF strike techniques. Results showed ankle and hip angle at IC, ankle ROM, peak ankle and knee extension moments, peak knee valgus moments, and ankle and knee negative peak net power between RF and FF strike patterns were significantly different (a < 0.05). These findings show foot strike technique during unplanned sidestepping can effect athlete lower-limb dynamics, where RF strike athletes may be at higher risk of ACL injury.